Platinum Nanoparticles to Study Metal Location in Shape-Selective Hydrocracking - Nel, Dayle (Centre for Catalysis Research, 2022)
In the petrochemical industry, bifunctional hydrocracking is used to further refine long chain hydrocarbon product molecules into smaller, more valuable fragments (such as diesel and aviation fuel). The current study is focused on using hydrocracking to increase diesel yield, as the preferred automotive fuel in terms of efficiency and environmental impact. However, even though conventional hydrocracking can significantly increase diesel yield, it is not selective to improving diesel quality. In a recent study by Brosius et al., 2016, the use of a Pt/MFI bifunctional hydrocracking catalyst in the presence of H2O has shown, for the first time, selective hydrocracking to produce not only a high yield but also high cetane number diesel product. The current study is a continuation of the work by Brosius et al., 2016, with a focus on improving the catalyst design and, in particular, the metal function, as in this study the Pt metal was supported using wet impregnation which does not allow for control of metal size and location. The hydrocracking mechanism consists of a (de)hydrogenation function at the metal sites and cracking/isomerisation steps at the acid sites. The reason a high yield of high cetane diesel is produced from hydrocracking over Pt/MFI in the presence of H2O is twofold: firstly, hydrocracking inside the MFI micropores is selective to C-type β-scission which results in linear cracking products, and secondly, H2O competes at the acid sites which allows for the desorption of the linear primary cracking products. From previous literature it is evident that metal location affects both activity and selectivity during hydrocracking over various catalyst types due to diffusion limitations. Furthermore, with hydrocracking over MFI, metal location is also expected to influence the amount of reactant molecules which crack inside the micropores. Therefore, the aim of this study was to quantify the extent that metal located inside or outside the micropores of MFI influences the cracking and isomerisation steps in the hydrocracking of n-C16 in the presence of H2O. Pt metal was selectively placed inside and outside the MFI micropores using different preparation techniques. To place the metal exclusively outside the micropores, monodisperse Pt NPs, which were bigger than the micropore diameter of 0.55 nm, were pre-synthesised and then contacted with the MFI support. To place the metal exclusively inside the micropores, a competitive ion exchange (CIE) method was used where Pt ions were chemically bonded within the MFI structure. Besides bulk MFI, the Pt NPs were also supported on MFI nanosheets (NS), which have been used in previous research to decrease diffusion limitations between metal and acid sites, to assess the effects of metal location. The prepared catalysts were characterised using TEM, ICP-OES, CO chemisorption, and NH3-TPD to ensure metal location was the only varied parameter. The catalysts were then analysed by dry and wet hydrocracking of n-C16 in a fixed-bed, trickle reactor, where the product composition was determined using an online GC. The performance of PtNPs/MFI and Pt-CIE/MFI were compared directly with Pt/MFI from Brosius et al., 2016. Catalyst activity was first analysed using conversion versus temperature plots and Arrhenius plots, primary hydrocracking was then assessed using C4/C12 ratio and once achieved, branched versus linear product selectivity could be compared. Looking at activity, H2O decreased the activity by ~30 °C, which is expected as H2O blocks acid sites. Comparing the individual samples showed relatively similar results in wet and dry hydrocracking, showing metal location does not play a major role in overall activity. From the Arrhenius plots, the activation energies could be compared and showed that the difference between wet and dry hydrocracking was relatable to the isosteric heat of adsorption of H2O on MFI. Primary hydrocracking was achieved for all three catalyst samples in the presence of H2O, again showing that metal location does not largely influence the yield of primary cracking products. However, when comparing branched versus linear primary cracking products, a significant difference was observed based on metal location. At low conversion, the greatest differences are seen, with Pt/MFI and Pt- CIE/MFI achieving ~100 % n-alkanes in C1-C15 cracked products, whereas PtNPs/MFI achieved only ~40 %. The reason for the vast differences is because having the metal inside the micropores, firstly, provides a non-diffusion hindered steady supply of reactant molecules to encourage desorption of the primary cracked products and, secondly, the cracking/isomerisation steps need to occur inside the MFI micropores which is more likely with internal metal. Furthermore, placing Pt NPs on NSs showed that even with thin NSs of 2 nm thickness, if the metal is placed outside, the hydrocracking products are just as branched as those from PtNPs/MFI. Post-mortem TEM characterisation of the catalyst samples revealed that no significant changes to the Pt metal sites were seen after ~10 days of reaction under varying hydrocracking conditions, ensuring that metal location was the only parameter varied in the study. In conclusion, regardless of metal location, primary hydrocracking can be achieved in the presence of H2O. Furthermore, placing metal exclusively inside the MFI micropores results in a significant increase in linear primary cracking products in comparison to placing metal completely outside the micropores, which results in mostly branched primary cracking products.